Application Of Surface Wave And Geoelectrical Resistivity Methods In Geotechnical Site Investigation - Khaizal, Khaizal (2013)
Many cases of constructions failure have been reported and the prohibitive cost of investigation has also increased due to the unavailability of subsurface information. The physical and mechanical behaviours of geological materials are commonly unpredictable. Lately conventional methods that include: drilling, cone penetration test (CPT), vane shear test, standard penetration test (SPT) have long been directly used in geotechnical site investigation for civil engineering purpose. Yet, in its implementation these methods required more cost compared to the total cost of construction project. Commonly three to five boreholes only, which geotechnical engineers using extrapolate method of boreholes to cover entirely site area. Advanced geophysical technologies are capable of solving these problems. These methods are relative more cost-effective, fast, non invasive and more robust of data acquired. Geophysical methods of surface wave and geo-electrical resistivity imaging methods were carried out at three investigation sites: Merbok Kedah, Balik Pulau and Nibong Tebal Pulau Pinang in Peninsular Malaysia. Continuous fixed roll along method was implemented for two dimensional surface wave field data acquisition. A Wenner-Schlumberger array was selected for geo-electrical resistivity imaging. The results of the study at the three sites showed that for Merbok site, the geophysical methods have successfully delineated residual soil over bedrocks and successfully detected marine sediments over weathered granitic bedrocks at Balik Pulau site as well as also reasonable results of detected low velocity zone at Nibong Tebal site.